2007
DOI: 10.1109/iembs.2007.4352608
|View full text |Cite
|
Sign up to set email alerts
|

The pupil as a possible premonitor of drowsiness

Abstract: Prediction of drowsiness based on an objective measure is demanded in machine and vehicle operations in which human errors may cause fatal accidents. Currently we focused on the pupil of the eye which is controlled by the autonomic nervous system, and easily observable non-invasively from the outside of the body. We employed uneventful driving simulation to induce drowsiness of human subjects, and an anti-saccade task to evaluate their cognitive and motor performance. First we confirmed that pupil diameter flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Human and animal studies demonstrate that non-luminance and non-accommodation changes in pupil diameter are related to a wide variety of mental and emotional factors, including arousal, attention, stress and cognitive load, and reveal a tight coupling between the state of the central and peripheral nervous systems12122232425262728293031323334353637383940.…”
Section: Discussionmentioning
confidence: 99%
“…Human and animal studies demonstrate that non-luminance and non-accommodation changes in pupil diameter are related to a wide variety of mental and emotional factors, including arousal, attention, stress and cognitive load, and reveal a tight coupling between the state of the central and peripheral nervous systems12122232425262728293031323334353637383940.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study did not investigate the relation between spontaneous pupillary oscillations (Henson and Emuh, 2010;Nishiyama et al, 2007;Wilhelm et al, 1998) and error profiles because consecutive points of missed pupil data in the epochs with longer consecutive errors were too long to interpolate a value into a series of pupil diameters by calculating results from surrounding raw pupil data. Second, we were unable to investigate the modest deterioration of vigilance weaker than we measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel work, over the last 50 years, waking brain state has been assessed in psychophysical experiments by monitoring the diameter of the pupil (Hess and Polt, 1960, 1964; Kahneman and Beatty, 1966). Human and animal studies have shown that changes in pupil diameter (after controlling for changes associated with luminance and depth accommodation) are correlated with arousal, attention, emotion, cognitive perception, “brain gain”, as well as heart rate and galvanic skin reflex, indicating a tight coupling between the state of the central and peripheral nervous systems (Alnaes et al, 2014; Bradley et al, 2008; de Gee et al, 2014; Einhauser et al, 2010; Einhauser et al, 2008; Eldar et al, 2013; Gilzenrat et al, 2010; Hess and Polt, 1960, 1964; Iriki et al, 1996; Jepma and Nieuwenhuis, 2011; Kahneman and Beatty, 1966; Murphy et al, 2011; Murphy et al, 2014b; Nassar et al, 2012; Nishiyama et al, 2007; Onorati et al, 2013; Preuschoff et al, 2011; Tursky et al, 1969; Wierda et al, 2012; Wilhelm et al, 2001). In human studies, drowsiness during the performance of a routine task, such as simulated driving, can be associated with wide variations in arousal and performance that are reflected by large fluctuations in pupil diameter (Kristjansson et al, 2009; Wilhelm et al, 2001).…”
Section: Variations In Pupil Diameter Track Changes In Brain Statementioning
confidence: 99%